Study of n-γ discrimination for 0.4-1 MeV neutrons using the zero-crossing method with a BC501A liquid scintillation detector - 陈永浩 雷家荣 张小东 安力 郑普 王新华 朱传新 何铁 (Chinese physics C, 2013)
An experimental system aimed at n-γ discrimination using the zero-crossing method with a φ3’’×2’’ BC501A liquid scintillation detector was established and tested with an Am-Be neutron source. Two-dimensional plots of energy versus zero-crossing time were obtained. The quality of n-γ discrimination was checked by the figure-of-merit （FOM）, the neutron peak-to-valley ratio, and the proportion of leaked neutrons over all neutron events. The performance of n-γ discrimination in terms of FOM was compared with previous work done by other groups. The n-γ discrimination in four different energy regions with an interval of 0.1 MeV between 0.3 MeV and 0.7 MeV was studied, and the results indicate that the n-γ discrimination threshold can go down to 0.4 MeV.